Tracing Pedagogical Progression on the Doctoral Level - Lappalainen, Pia Helena (International Journal of Engineering Pedagogy (iJEP), 2018)
While much has been written about cognition and intellect as factors enhancing researcher productivity, less is known about the mental processes impacting scholarly endeavors. The anxiety stemming from such vast and solitary projects as thesis writing has been recognized, but the literature on doctoral study has been more silent on pedagogies supporting thesis completion. To design effective pedagogies mediating postgraduate degree completion and promoting research quality, this article traces pedagogical progression on the doctoral level. As a modest empirical effort investing in affective learning, this work analyses doctor-al students’ needs for instructional writing support. The analysis reveals unmet needs that undermine student well-being, engagement, and writing progress. The qualitative analysis of 93 engineering candidates’ responses directs the pedagogic focus in doctoral writing away from language proficiency towards holistic con-sideration of learner needs, especially in terms of the affective load involved in thesis writing. This article aims to decelerate the trend towards decreased contact hours on the doctoral level through empirically-derived evidence highlighting the importance of face-to-face instruction. As pedagogy, this study proposes 1) participation in the research community of practice through peer reviews to intensify mimicry strategy in adopting expertise, and 2) teacher immediacy as means of promoting the quality of the mentor-mentée relationship and of ultimately expedit-ing research progress and degree completion.